Redesigning a sustainable bioenergy system using a multi-platform application. (February 2020) - Nur, S M; Ariati, R; Yandri, E; Adiatmojo, G D; Abdullah, K
Abstract: This article is a concept that arranges and expands the bioenergy system paradigm that has been widely published by renewable energy experts. The new paradigm is based on the principle of the energy system where all factors must be identified and included because they affect the sustainability of the system's process, performance and results. The target of this concept is structuring a more holistic and effective analytical technique to guide policymakers, entrepreneurs, and researchers in making decisions and implementing bioenergy projects. The literature review is used as an analytical tool to build this concept and the results of a study indicate that the bioenergy system is all key components that can be grouped into policy and regulation subsystems; the subsystem of the production and bioenergy utilization chain, the bioenergy management subsystem; and the bioenergy infrastructure subsystem. To get sustainability, bioenergy system is necessary to link and identify key materials that are related and interact with the economic, social and environmental pillars that support the sustainable development system. Future prospects are translating the concept of bioenergy system and their constituent components into mathematical models, making a research guide in the future based on agro-industry and regional agro-bioenergy system in Indonesia.